Implementation of the regulations of the board of directors of TVRI public agency on Non-Civil Servant in public television broadcasting agency in Indonesia - Noi, Erasmus Nagi; Liliweri, Alo; Tammunu, Lenny N. (goodwood publishing, 2019)
Purpose: This research aims to analyze the implementation of the regulation of the board of directors of the TVRI public broadcasting institution regarding non-civil servants (Study at the Indonesian Television Public Broadcasting Institute (TVRI), East Nusa Tenggara Station. Research methodology: In this study, the authors used an interpretive research paradigm. The interpretive approach aims to understand the